Airisms from the four winds: The Bremen [re abandoned airplane on Greenly Island, Labrador]
A short note about the abandoned aircraft Bremen on Greenly Island, Labrador. Periodical covers have been included with many of the digitized articles whether they relate to them or not. Extra pages not part of the article in question may also be present.